Synthesis of Biotin-Tagged Chitosan Oligosaccharides and Assessment of Their Immunomodulatory Activity - Tsvetkov, Yury E.; Paulovičová, Ema; Paulovičová, Lucia; Farkaš, Pavol; Nifantiev, Nikolay E. (Frontiers in Chemistry, 2020)
Chitin, a polymer of β-(14)-linked N-acetyl-D-glucosamine, is one of the main polysaccharide components of the fungal cell wall. Its N-deacetylated form, chitosan, is enzymatically produced in the cell wall by chitin deacetylases. It exerts immunomodulative, anti-inflammatory, anti-cancer, anti-bacterial, and anti-fungal activities with various medical applications. To study the immunobiological properties of chitosan oligosaccharides, we synthesized a series of β-(14)-linked glucosamine oligomers comprising 3, 5, and 7 monosaccharide units equipped with biotin tags. The key synthetic intermediate employed for oligosaccharide chain elongation, a disaccharide thioglycoside, was prepared by orthogonal glycosylation of a 4-OH thioglycoside acceptor with a glycosyl trichloroacetimidate bearing the temporary 4-O-tert-butyldimethylsilyl group. The use of silyl protection suppressed aglycon transfer and provided a high yield for the target disaccharide donor. Using synthesized chitosan oligomers, as well as previously obtained chitin counterparts, the immunobiological relationship between these synthetic oligosaccharides and RAW264.7 cells was studied in vitro. Evaluation of cell proliferation, phagocytosis, respiratory burst, and Th1, Th2, Th17, and Treg polarized cytokine expression demonstrated effective immune responsiveness and immunomodulation in RAW264.7 cells exposed to chitin- and chitosan-derived oligosaccharides. Macrophage reactivity was accompanied by significant inductive dose- and structure-dependent protective Th1 and Th17 polarization, which was greater with exposure to chitosan- rather than chitin-derived oligosaccharides. Moreover, no antiproliferative or cytotoxic effects were observed, even following prolonged 48-h exposure. The obtained results demonstrate the potent immunobiological activity of these synthetically prepared chito-oligosaccharides.